Nationalitarism and democracy: for the reexamination of the national question - Rodrigues de Almeida, Lúcio Flávio (Pontifícia Universidade Católica de São Paulo, 2004)
The main hypothesis of this article is that “nationalitarism”, thisdemocratic existing aspect of the nationalism of an “oppressednation” is not always linked to political-ideological programs ofthe dominated classes. On the contrary, this link is a potential resultof the struggles of these classes.